Systematic literature review: Theory on GVCs' impact on wages, employment, and productivity - Sabina Szymczak (Gdansk University of Technology, Faculty of Management and Economics, 2023)
This study presents a systematic literature review (SLR) to provide a collection of theories explaining the impact of global value chains (GVCs) on labour market outcomes. Due to the complex nature of GVCs and the interconnectedness of wages, employment, and productivity, many direct and indirect effects are at play. To ensure a transparent and systematic flow of the review process, I follow the PRISMA guide. Eventually, 36 records out of 1221 results from Scopus database were selected for full-text analysis. This SLR may be useful for theorists, empirical economists, and policy makers as an up-to-date overview of theoretical developments and convenient map of potential outcomes expected from involvement in GVCs. It identifies and systematizes a number of effects existing in the literature under various names. Additionally, it shows the shortcomings of the existing theories. They often adopt the perspective of developed country trading with developing one, while nowadays the intermediate trade occurs in many forms, affecting various actors. Less aggregated levels of analysis could be a great input to the discussion, as well as addressing different GVCs' dimensions and types of organisation. The understanding of relation between GVC position and labour market is especially worth exploration as the existing evidence adopt different and even contradicting perspectives on the definition of upgrading the GVC position.
Keywords: F16; F60; 330; systematic literature review; global value chains; wage; employment; productivity